Gene expression profiling for human iPS-derived motor neurons from sporadic ALS patients reveals a strong association between mitochondrial functions and neurodegeneration - Alves, Chrystian J.; Dariolli, Rafael; Jorge, Frederico M.; Monteiro, Matheus R.; Maximino, Jessica R.; Martins, Roberto S.; Strauss, Bryan E.; Krieger, José E.; Callegaro, Dagoberto; Chadi, Gerson (Frontiers in Cellular Neuroscience, 2015)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease that leads to widespread motor neuron death, general palsy and respiratory failure. The most prevalent sporadic ALS form is not genetically inherited. Attempts to translate therapeutic strategies have failed because the described mechanisms of disease are based on animal models carrying specific gene mutations and thus do not address sporadic ALS. In order to achieve a better approach to study the human disease, human induced pluripotent stem cell (hiPSC)-differentiated motor neurons were obtained from motor nerve fibroblasts of sporadic ALS and non-ALS subjects using the STEMCCA Cre-Excisable Constitutive Polycistronic Lentivirus system and submitted to microarray analyses using a whole human genome platform. DAVID analyses of differentially expressed genes identified molecular function and biological process-related genes through Gene Ontology. REVIGO highlighted the related functions mRNA and DNA binding, GTP binding, transcription (co)-repressor activity, lipoprotein receptor binding, synapse organization, intracellular transport, mitotic cell cycle and cell death. KEGG showed pathways associated with Parkinson’s disease and oxidative phosphorylation, highlighting iron homeostasis, neurotrophic functions, endosomal trafficking and ERK signaling. The analysis of most dysregulated genes and those representative of the majority of categorized genes indicates a strong association between mitochondrial function and cellular processes possibly related to motor neuron degeneration. In conclusion, iPSC-derived motor neurons from motor nerve fibroblasts of sporadic ALS patients may recapitulate key mechanisms of neurodegeneration and may offer an opportunity for translational investigation of sporadic ALS. Large gene profiling of differentiated motor neurons from sporadic ALS patients highlights mitochondrial participation in the establishment of autonomous mechanisms associated with sporadic ALS.